(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVE: To assess outcomes 24 months after treatment start for multidrug-resistant tuberculosis (MDR-TB). METHODS: Cohort study of all culture-positive MDR-TB cases notified in Switzerland from 01/2003 to 07/2010. RESULTS: Fifty-one cases were observed, with a median age of 26 years (range 2–56). Twenty-seven were male, five of Swiss origin, 46 of foreign origin (Asia 18, Africa 13, former Soviet Union 8), including 21 asylum seekers and refugees. Twelve had received a previous treatment for TB and 24 had not (15 unknown). Forty-four cases were pulmonary of which 25 were known to be sputum smear positive. All but two strains showed additional resistances: 29 to ethambutol, 27 to pyrazinamide, 6 to a fluoroquinolone, 5 to amikacin. None was resistant to both of the latter two classes. Molecular analyses showed three pairs of identical strains. Fluoroquinolones were used in 48 patients and second-line injectable drugs in 37. The median duration of MDR treatment was 18 months (range 1–26). The outcome after 24 months was successful in 39 (76%) and unsatisfactory in 12 (24%) patients: two deaths from TB; two treatments terminated owing to side effects of drugs and one owing to pregnancy; four defaults from treatment at months 0, 4, 8, and 21; two transfers abroad with unknown outcome; one outcome unknown. There was no significant association of unfavourable outcomes with age, sex, origin, previous treatment, treatment delay, resistance pattern, and classes of drugs used. CONCLUSIONS: MDR-TB in Switzerland occurs mostly in persons of foreign origin. Results of decentralised treatments were satisfactory.